2022
DOI: 10.1111/ene.15327
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cortical atrophy: Primary occipital variant

Abstract: Background Posterior cortical atrophy (PCA) is one of the atypical Alzheimer's disease variants, characterized by predominant visuospatial and visuoperceptual deficits, with established dorsal and ventral subtypes. A third primary occipital (caudal) variant has been suggested. We aimed to determine its demographics, clinical manifestations, and biomarker findings. Methods Fifty‐two PCA patients were investigated. Patients underwent neuropsychological assessment, magnetic resonance imaging, and fluorodeoxygluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…1). This third phenotype is also characterized by a less important hypometabolism in temporal-parietal regions compared with the other two variants [20 ▪▪ ]. Clinically, these patients have less ideomotor apraxia, absence of parkinsonism, and a milder degree overall symptom severity, including fewer neuropsychiatric features compared to the more documented phenotypes.…”
Section: Posterior Cortical Atrophymentioning
confidence: 87%
See 1 more Smart Citation
“…1). This third phenotype is also characterized by a less important hypometabolism in temporal-parietal regions compared with the other two variants [20 ▪▪ ]. Clinically, these patients have less ideomotor apraxia, absence of parkinsonism, and a milder degree overall symptom severity, including fewer neuropsychiatric features compared to the more documented phenotypes.…”
Section: Posterior Cortical Atrophymentioning
confidence: 87%
“…Neuroimaging features (Structural MRI on the left, fluorodeoxyglucose (FDG)-PET in the center, and amyloid- and tau-PET on the right) observed in the subvariants of posterior cortical atrophy: (A) primary occipital variant; (B) Dorsal variant; (C) Ventral variant. Reproduction from [20 ▪▪ ].…”
Section: Posterior Cortical Atrophymentioning
confidence: 99%
“…Further evidence for a key role of the primary visual cortex in the appearance of colorfulness comes from a recent study by Shir et al 50 , which reported a primary occipital variant of posterior cortical atrophy, a rare form of dementia which primarily affects visuospatial functions in early disease stages. The authors found no significant differences in higher-order object and space perception between the different PCA phenotypes included in the study, but the occipital variant of PCA was found to be associated with poor performance on the Ishihara test for color perception, which is indicative of an acquired Red—Green color-blindness due to neurodegeneration of the visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing our knowledge on this topic will improve our understanding of the neurobiology of color perception, and has practical implications for everyday color use and applications designed for older adults. It will furthermore enrich our understanding of later-life neurodegenerative diseases (e.g., Alzheimer’s disease, posterior cortical atrophy (PCA), and Parkinson’s disease), which often affect the visual system as well 48 50 . In this study we aimed to address this by modelling the effects of color lightness and chroma (colorfulness) on pupil responses in young and older adults, in a closely controlled passive viewing experiment with 26 broad-spectrum digital color fields.…”
Section: Introductionmentioning
confidence: 99%
“…The last is a rare occipital form characterized by visual field defects, such as homonymous hemianopia or quadrantanopia, and a diminished visual acuity subtype [74,79,81,82]. In a recent study [83], 52 PCA patients underwent magnetic resonance imaging, fluorodeoxyglucose (FDG)-, amyloid-, and tau-positron emission tomography (tau-PET) scans, as well as a neuropsychological assessment. Only nine patients were classified as primary occipital; they were older and had more years of education than the others.…”
Section: Symptomatology and Clinical Featuresmentioning
confidence: 99%